Cortico-therapy in a dog with septic shock not responsive to vasopressors: A case report - Barbosa, Breno; Alves, Fernanda dos Santos; Coelho, Nathália das Graças Dorneles; Oliveira Pinto, Paula Costa de; Beier, Suzane Lilian; Freitas, Patrícia Maria Coletto (Pubvet, 2018)
Septic shock, a consequence of severe sepsis with hypotension that is not responsive to volume replacement, is quite common in veterinary medicine, and its occurrence may be consorted with absolute or relative deficiency of corticosteroid hormones, thus requiring replacement of these. A dog was treated at the Veterinary Hospital in septic shock, therapy was started with crystalloid solution, followed by vasopressors, and there was no improvement in the animal’s picture. Twenty-four hours after the start of this treatment, hydrocortisone was administered, and then gradual improvement in hemodynamic parameters was observed. After 3 days of hydrocortisone use, a significant improvement in the clinical picture of the animal was observed. Thus, it is concluded that the use of corticosteroids may be necessary in patients with septic shock who are not responsive to the vasopressors.